Skrining Resep Polifarmasi Secara Klinis Pada Pasien Hipertensi Di Rumah Sakit Advent - Razoki Razoki; Rezki Sari Harahap; Novitaria Br Sembiring; Elfia Neswita (Journal of Pharmaceutical and Sciences, 2023)
Introduction: The use of drugs in inappropriate amounts or doses is known as polypharmacy. The development of polypharmacy and the complexity of drugs currently used in medicine allowed a huge increase in drug interactions. Method: The method used in this study is a descriptive method and data collection is carried out retrospectively. This study was conducted with the aim of finding out more about the description of drug interaction events in patients diagnosed with hypertension. Results: The collected prescriptions were those received by IFRS Advent Medan in October-December 2022 as many as 500 prescriptions. The next step, prescriptions are screened and adjusted to the categories of inclusion and exclusion requirements. Prescriptions that meet the inclusion category are original prescriptions with a minimum of 3 drugs, a total of 132 prescriptions. So in this article, a completeness analysis of polypharmacy prescriptions was carried out based on clinical studies of 132 prescriptions. Conclusion: The accuracy of indications, drug dosage, rules, methods, and duration of use of the complete drug is 100%, The prescription contains 3 drugs, there are 7 interacting prescriptions (54%) out of a total of 13 prescriptions.